2014
DOI: 10.1002/gps.4118
|View full text |Cite
|
Sign up to set email alerts
|

Service utilisation and family support of people with dementia: a cohort study in England

Abstract: Caring for people with dementia at home may be more expensive, and more stressful for carers, than care in residential settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
0
9
1
Order By: Relevance
“…Long-term family conflict over care provision may lead to the person with dementia being admitted into a care home. 47 In measuring levels of stress in carers of people with dementia, Gage et al 48 found that this was significantly reduced when the person they cared for was admitted to residential care.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term family conflict over care provision may lead to the person with dementia being admitted into a care home. 47 In measuring levels of stress in carers of people with dementia, Gage et al 48 found that this was significantly reduced when the person they cared for was admitted to residential care.…”
Section: Resultsmentioning
confidence: 99%
“…Of the ten studies, four (five papers) were from the USA, 17 , 25 , 45 47 three from the UK, 48 50 two (four papers) from Australia, 51 54 and one from Taiwan. 55 Three studies used a cross-sectional telephone survey, 17 , 45 , 47 three studies conducted qualitative interviews with carers, 49 , 51 53 , 55 and three studies utilized a mixed methods approach.…”
Section: The Experience Of Hospital Discharge Planning For Family Carmentioning
confidence: 99%
See 1 more Smart Citation
“…Other benefits from outdoor walking group activities include: continuity of self and identity [ 4 6 ]; raised self-esteem, pleasure derived from observing nature, spatial awareness, mood upliftment, reduced agitation, relaxation, improved communication and, enjoyment from sensory stimulation [ 7 , 8 ]. Physical and psychological benefits apart, walking as part of a group can enable people with dementia to become (or remain) part of social networks [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although costs of dementia care to society are high, the burden of care falls disproportionately on unpaid carers [5][6][7][8]. Previous UK person-level studies of care for people with dementia [9][10][11][12][13][14][15] have used relatively small samples, covered limited geographical areas, or focused on unconfirmed diagnoses or diagnosis of a single dementia type. This limits the information available to decision makers planning how to meet the needs of people living with dementia and their families [16,17].…”
Section: Introductionmentioning
confidence: 99%